Efficacy and safety of transarterial embolization in patients with intraabdominal hemorrhage: Experience from two centers (Annals of Medical Research, 2023)
Aim: To evaluate the safety, efficacy, and clinical outcomes of transarterial embolization (TAE) in patients with intraabdominal hemorrhage.Materials and Methods: Eighty-one patients who underwent intraabdominal TAE between January 1, 2020, and March 1, 2023 were evaluated retrospectively. Patients who underwent transarterial chemoembolization (n=15), mass embolization (n=12), and venous embolization (n=4) were excluded. Patient characteristics, hemorrhage etiology, embolized arteries, embolizing agents used, clinical and technical success, and rebleeding and in-hospital mortality rates were recorded.Results: A total of 50 patients (37 males, 74%) were included in the study. The mean age of patients was 53.4±21.1 years. The most common pathology causing hemorrhage was upper gastrointestinal bleeding due to peptic ulcers (n=21, 42%), followed by tumors (n=8, 16%), iatrogenic causes (n=8, 16%), and trauma (n=6, 12%). The most commonly used embolizing agents were isolated coil (n=26, 52%) and a combination of coil and polyvinyl alcohol (n=12, 24%). The rate of technical success was 98% (n=49/50), and catheterization could not be performed in only one of the patients due to advanced vasospasm in the first procedure. After the first angiography, rebleeding occurred in 8% (n=4) cases, of which three were due to peptic ulcers and one was related to gastric cancer. One of these patients died in hospital, while the remaining three were discharged. The rate of in-hospital mortality was 16% (n=8) in all patients, and the clinical success rate was 84% ​​(n=42).Conclusion: TAE provides high rates of immediate and complete hemostasis with low complication rates. It is an effective method, especially for solid organ injuries and in the management of bleeding complications after surgery or intervention.
Keywords: Arterial embolization; Intraabdominal hemorrhage; Endovascular treatment; Gastrointestinal bleeding